The Role and Authority of the Directorate General of Intellectual Property in Handling Complaints of Copyright Infringement in Indonesia - Ardiansyah, Erlan; Rachman, Rahmia; Datupalinge, Suarlan; Kemala Sari, Dewi (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2023)
The rise of copyright infringement that occurred in Indonesia is very alarming, even the act of infringement seems to have been regarded as a common thing. DJKI is a government agency that organizes the formulation and implementation of policies in the field of intellectual property in accordance with the provisions of legislation, of course expected to provide copyright protection in Indonesia. The research method used is Normative Empirical, using a statutory approach that is analyzed qualitatively. DJKI has a role as a regulator, as an administrator, law enforcement, and dissemination of intellectual property, as well as the authority to receive and handle complaints of intellectual property violations in accordance with applicable procedures up to the stage of the prosecution process. It is recorded that the number of complaints submitted to the DJKI from 2019 to 2022 is 155 complaints and all of these complaints have been resolved by the DJKI, one of the complaints is copyright infringement that occurred in Central Sulawesi is a case of copyright infringement of Hasan Bahasyuan’s song, this complaint has also been resolved by the DJKI through a mediation process so that the case does not proceed to court. So it can be seen that DJKI has an important role in copyright protection in Indonesia.